Exploring the gut microbiome and serum metabolome interplay in non-functioning pituitary neuroendocrine tumors - Jifang Liu; Jifang Liu; Zhang Ye; Zhang Ye; Yi Zhang; Yi Zhang; Wan Su; Wan Su; Jie Liu; Jie Liu; Tianqi Chen; Yanan Shi; et al. (Frontiers in Microbiology)
The gut microbiome has emerged as a potential factor in cancer pathogenesis, but its role in non-functioning pituitary neuroendocrine tumors (NF-PitNETs) remains unclear. This study aimed to elucidate gut microbiome and metabolomic alterations in NF-PitNETs by comparing microbial diversity, pathogenic bacteria, and serum metabolomic profiles between NF-PitNET patients and healthy controls. The gut microbiome was assessed through 16S rRNA sequencing, while serum metabolomics was analyzed using mass spectrometry. Correlation analyses identified potential links between microbial characteristics and metabolic markers. The results revealed that specific pathogenic bacteria, such as Bacteroides, were significantly enriched in NF-PitNET patients. Multi-omics correlations suggested that altered microbiota might contribute to NF-PitNET pathogenesis by modulating host metabolic pathways. These findings highlight the potential role of gut microbiome dysbiosis and its metabolic effects in NF-PitNET development, offering insights into possible therapeutic and diagnostic targets.